Unveiling microbiome diversity and abundance in the ceca and intestine of freshly slaughtered market-sold kampung chickens - RETNO MURWANI; ANDRIANUS SEMBIRING; NI KADEK DITA CAHYANI; AJI WAHYU ANGGORO; EKA MAYA KURNIASIH; ANTO BUDIHARJO; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Murwani R, Sembiring A, Cahyani NKD, Anggoro AW, Kurniasih EM, Budiharjo A, Ambariyanto A. 2025. Unveiling microbiome diversity and abundance in the ceca and intestine of freshly slaughtered market-sold kampung chickens. Biodiversitas 26: 909-919. The native Indonesian kampung chicken is a popular and desirable meat source sold live at traditional markets, offering fresh meat for consumers. The aim of this research was to investigate the microbial diversity of intestines and cecum of freshly sacrificed female kampung chickens using genomic sequencing. The DNA from 50 samples of female kampung chickens was extracted and amplified by PCR targeting the 16S rRNA V4 region. The PCR products were sequenced, and the taxonomic composition was summarized using the Phyloseq package, with taxa merged at six levels: domain, phylum, class, family, genus, and species. The result showed that the microbiome was dominated by Firmicutes (61.22%), Bacteroidota (20.06%), Actinobacteriota (7.14%), and Proteobacteria (2.81%). Lactobacillus aviarius (2.82%) was abundant across the samples. The cecum exhibited more diverse microbiomes than the intestines, with a predominance of Firmicutes. Beneficial bacteria, such as L. aviarius (5.26%) and Bacteroides barnesiae (3.03%), were dominant in the small intestine and cecum, respectively. A significant portion of the sequences remained unidentified or uncultured (50.95% and 20.61%, respectively). The gut microbiome of market-sold, freshly sacrificed female kampung chickens displays remarkably high diversity and richness, characterized by beneficial bacterial abundance, crucial for maintaining the chickens' overall health. These findings strongly support the consumer preference for fresh female kampung chicken meat, validating the traditional choice of the local community.